Evaluation of ajowan (Trachyspermum ammi L.) introductions for growth, yield and quality - Chattopadhyay, S Datta, R Chatterjee, P S Medda, P K (Journal of Spices and Aromatic Crops, 2001)
Five ajowan (Trachyspermum ammi L.) introductions (RA-6, HAJ-S-I, RA-2, RA-7 and RA-4) and a local cultivar were evaluated for their growth, yield and quality under alluvial zone of West Bengal (India). Among the introductions, RA-2 exhibited superiority over other introductions in respect of morphological characters such as plant height, number of primary branches per plant and number of leaves per plant and seed yield. The essential oil content was significantly higher in local cultivar (4.53%), while essential oil yield per hectare was significantly higher in RA-7 (14.50 kg) which was on par with RA-4 (14.13 kg).